Transparency and Accountability of Financial Management of the National Awakening Party Financial Year 2019-2022 - Rika Puspita Muliahati; Nurfitri Nugrahaningsih; Erdi Erdi (International Journal Labs, 2023)
This study is entitled “Transparency and Accountability of Financial Management of The National Awakening Party Financial Year 2019-2022.” The research problem was that the Central Board of The National Awakening Party (DPP PKB) had not fulfilled the statutory law on transparency of financial management, and there was a tendency to increase the amount of Political Party Financial Assistance year after year. However, this fund increase has not been accompanied by efforts to administer the National Awakening Party's finances in an accountable manner. This research explores the implementation of transparency and accountability indicators for FY 2019-2022. For the research, the transparency indicator was taken from the theory of transparency by Krina L (2003), while the accountability indicator was taken from the theory of Elwood (cited in Mardiasmo, 2008). Of the five indicators, only one indicator, accountability in preventing waste, leakage, and corruption, has been effectively implemented. According to the idea of Nambo and Puluhulawa (2005), this is due to the interests of political organizations that still prioritize group interests in government, where these interest groups tend to desire to maintain their political power solely. This research recommends that a political party establish a paradigm regarding the need for a balance between party and public interests, recruit competent digital operators, coordinate well with authorized institutions in publishing annual reports, and appoint a responsive person in charge of managing financial governance reports and complaints. The person must be competent in digital recording, reporting, and distribution for DPP PKB to optimally implement the remaining four indicators of transparency and accountability practices.